Persepsi Pengguna terhadap Perangkat Lunak Akuntansi Usaha Kecil Berbasis Cloud - Mayasari, Mega; Supardianto, Supardianto; Irawati, Rusda; Lawita, Nadia Fathurrahmi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2025)
This article discusses the development and evaluation of BANTU UMKM, a cloud-based financial recording application designed to enhance the capacity of Micro, Small, and Medium Enterprises (MSMEs) in preparing simple financial reports efficiently and accurately. Following an initial trial with the TDA MSME community, the study expanded its testing to 20 MSMEs under the guidance of PLUT KUKM in Batam City. User satisfaction was assessed using the End User Computing Satisfaction (EUCS) framework, which encompasses five dimensions: content, accuracy, format, ease of use, and timeliness. The findings indicate a high level of user satisfaction, particularly in terms of information clarity, system accuracy, relevant output, and timely access to information. A key innovation of this application lies in the automated accounting logic embedded behind the user interface.